Male Adolescents’ Gender Attitudes and Violence: Implications for Youth Violence Prevention - Miller, Elizabeth (Am J Prev Med, 2019)
INTRODUCTION: This study analyzed the associations among male adolescents’ gender attitudes, intentions to intervene, witnessing peers’ abusive behaviors, and multiple forms of adolescent violence perpetration. This community-based evaluation aims to inform future youth violence prevention efforts through the identification of potential predictors of interpersonal violence perpetration. METHODS: Cross-sectional data were from baseline surveys conducted with 866 male adolescents, aged 13—19 years, from community settings in 20 lower-resource neighborhoods in Pittsburgh, PA (August 2015 — June 2017), as part of a cluster RCT to evaluate a sexual violence prevention program. Participants completed in-person, anonymous electronic surveys about gender attitudes, bystander intentions, witnessing peers’ abusive behaviors, violence perpetration, and demographics. The analysis was conducted between 2018 and 2019. RESULTS: The youth identified mostly as African American (70%) or Hispanic, multiracial, or other (21%). Most (88%) were born in the U.S., and 85% were in school. Youth with more equitable gender attitudes had lower odds of self-reported violence perpetration across multiple domains, including dating abuse (AOR=0.46, 95% 0=0.29, 0.72) and sexual harassment (AOR=0.50, 95% 0=0.37, 0.67). The relationship between intentions to intervene and violence perpetration was inconclusive. Witnessing peers engaged in abusive behaviors was associated with increased odds of multiple types of violence perpetration, such as dating abuse (witnessed 3 or more behaviors, AOR=2.41, 95% CI=1.31, 4.44). CONCLUSIONS: This is the first U.S.-based study to elicit information from male adolescents in community-based settings (rather than schools or clinics) about multiple types of interpersonal violence perpetration. Findings support violence prevention strategies that challenge harmful gender and social norms while simultaneously increasing youths’ skills in interrupting peers’ disrespectful and harmful behaviors.